INFLUENCE OF NOSE TAMPONADE ON QUALITY OF LIFE IN THE EARLY POSTOPERATIVE PERIOD AFTER SEPTOPLASTY - Kwang Hyun Kim (International Scientific and Current Research Conferences, 2021)
Surgical treatment is the only method for correcting a deviated nasal septum. Most of surgeons’ complete surgery on the nasal septum with anterior tamponade of the nasal cavity, which is necessary to fix the osteomeotal reconstructed flap in the median position, as well as to prevent complications such as bleeding, hematoma in the early postoperative period, and the formation of synechiae between of wall in the nasal cavity. For tamponade, in most cases, gauze tampons soaked in anti-inflammatory ointment are used. Despite the good fixing effect, such a tamponade completely turns off the main functions of the nose for the entire period - respiratory, drainage, protective; there is no ventilation of the paranasal sinuses, ventilation of the middle ear is impaired. Tamponade causes compression of the injured mucous membrane, and, consequently, ischemia, up to perforation of the septum and pain (especially during removal), trauma to the mucous membrane, lacrimation, discomfort when swallowing, sleep disturbances, increased blood pressure, headache due to disturbed microcirculation in the vessels of the head brain, creates a good environment for the reproduction of a bacterial agent with a rarely occurring syndrome of infectious-toxic shock.